The practice of survey research: theory and applications - Ruel, Erin E. (Sage, 2016)
Unique in its integration of theory and application, this comprehensive book explains survey design, implementation, data analysis, and continuing data management, including how to effectively incorporate the latest technology (e.g., SurveyMonkey and Qualtrics). Data management and analysis are demonstrated and explained through statistical software including SPSS, SAS, and STATA. In addition to helping students develop a complete understanding of survey research from start to finish, the authors also address the challenges and issues of specific disciplines.